The effects of factor and sector biased technical change revisited - Robert Stehrer (FIW - Research Centre International Economics, 2007)
In the trade-technology-wage debate, the effects of the various forms of technical progress on relative factor prices have been addressed in a number of contributions over the past decade. However, the existing literature is far from conclusive. The various contributions have either relied on specific assumptions, such as Leontief technologies or Cobb-Douglas demand, that have been decisive for the respective conclusions, or they used a more general framework, arriving at ambiguous results in many cases. In this paper we analyse a general equilibrium framework with CES production and CES demand functions, which allows for any discrete number of sectors and countries integrated via trade flows. Technologies are country- and sector-specific and endowment structures differ across countries. The necessary and sufficient conditions under which the relative wage rates are rising or falling in the domestic and foreign economies are derived. This is done for various types of factor- and sector-biased technical change taking place in a particular sector in either the home or foreign country. The conditions - depending on the relative skill intensity of the innovating sector, the elasticities of substitution in demand and supply, the relative factor endowment and the prevailing (equilibrium) relative wage rate - allow for straightforward economic interpretations. This permits to solve the cases classified as ambiguous in the existing literature and provides clear-cut conditions which are important for modelling and empirical research. Furthermore, the results are interpreted with respect to recent empirical studies where special emphasis is given to the sector-biased versus factor-biased hypothesis.
Keywords: C62; C68; F16; O33; 330; Trade; technology; wage debate; wage; CES production; CES demand; CES; trade flows; general equilibrium; skill intensity; skill; factor endowment